Occuli dextra proptosis in symptomatic hiperthyroidism with diffuse goitre in 45 year old woman: A case report with literature review - Timotius, Timotius; Putra, Ananda; Johansen, Johansen; Titanic, Pussof Yayazucah; Novitasari, Diana (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Hyperthyroid is refers to increased of thyroid synthesis hormon production by the thyroid gland that cause an excessive amount thyroid homrone circulate in the blood and eventually cause protrusion of unilateral or both eyes at the anterior out of the orbit due to an increased orbital content within the rigid bony orbit. We report the case of 45 -year-old woman with major complaints of blurred vision on her right eye. Blurred vision on this patient is without a red eye but have a tension on his eye that feel like going out. On local examination of the neck area, there was visible mass during inspection, and on palpation there mass in the neck area. On laboratory examination, TSHs levels were 0.085 uIU/mL, FT4 levels were 12.8 pmol/L, creatinine was 0.9 mg/dL, Calcium was 1.23 mmol/L, Natrium 134 mmol/L, Kalium 3.30 mmol/L. On Colli ultrasound, multiple lymphadenopathy were found on the right and left Colli measuring 1.65 cm x 0.6 cm in the right Colli and 2.10 cm x 0.35 cm in the left Colli and on Head CT-scan with contrast orbita centration, Brain edema and proptosis on occuli dextra were found. The patient underwent oral therapy using propylthiouracil and intravenous methylprednisolone therapy. Administered intravenous methylprednisolone pulse therapy show a significant decrease on grave opthalmopathy severity.